Clear-cut and substrate characteristics important for the occurrence of the beetle Upis ceramboides - Naalisvaara, Ronny (SLU/Dept. of Ecology, 2013)
Disturbances, such as fire and wind, are important for saproxylic beetles (= beetles depending on decaying wood) to gain substrate in boreal forests. Clear-cutting is an example of a man-made disturbance. Measures such as prescribed burning have been made to resemble natural disturbances. The aim of this study was to see which clear-cut characteristics are important for the occurrence of the saproxylic beetle Upis ceramboides.